Ecology and Energetics of Early Food Production in the Near East and North Africa - Russell, Kenneth Wayne
Ph.D. Dissertation; Chairman: Dennis L. Heskel. Order No. DA8706379; DissAbstr 47/12 (June 1987) 4427-A.